Intellectual property as a carrot for innovators: using game theory to show the limits of the argument - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2007)
Policymakers all over the world claim: no innovation without protection. For more than a century, critics have objected that the case for intellectual property is far from clear. This paper uses a game theoretic model to organise the debate. It is possible to model innovation as a prisoner's dilemma between potential innovators, and to interpret intellectual property as a tool for making cooperation the equilibrium. However, this model rests on assumptions about cost and benefit that are unlikely to hold, or have even been shown to be wrong, in many empirically relevant situations. Moreover, even if the problem is indeed a prisoner's dilemma, in many situations intellectual property is an inappropriate cure. It sets incentives to race to be the first, or the last, to innovate, as the case may be. In equilibrium, the firms would have to randomise between investment and non-investment, which is unlikely to work out in practice. Frequently, firms would have to invent cooperatively, which proves difficult in larger industries.
Keywords: C72; O31; K11; 330; intellectual property; game theory; Immaterialgüterrechte; Innovation; Ökonomischer Anreiz; Kritik; Innovationswettbewerb; Spieltheorie; Theorie